Spiritual awareness and interfaith relations - Kartupelis, Jenny (Journal for the Study of Spirituality, 2017)
This article is based on presentations and discussion that took place at a Symposium entitled Promoting Spiritual Life: An Interfaith Perspective, held at Sarum College, Salisbury, UK, on 4 February 2016. The event was organized by the World Congress of Faiths to launch the celebrations of its 80th Anniversary. The concept and importance of spirituality in an apparently more secular society are explored, and the holistic nature of personal spiritual experience is argued on the basis of accounts collected and analysed. The debate then moves on to a consideration of these observations in the context of interfaith encounters being required to reject false dichotomies; and the engagement of religions in civic space, of which interfaith dialogue and activity is a vital part. It concludes that the potential for spiritual connection can play a powerful role in challenging traditional blocks to relationships between faiths.